The anthropology of morality a dynamic and interactionist approach - Heintz, Monica (Routledge, an imprint of the Taylor & Francis Group, 2021)
"Why, when and where are some moral systems supported and followed whilst others are condemned? Are moral values relative or universal? Can immoral actions be tolerated in times of crisis? Is the dream of becoming better sufficient for prompting virtuous behavior, or should we dream about what is best? Do moral values last? The divergence in practices and codes of moral belief and action present significant challenges but also offer opportunities to anthropologists for understanding social life. In this book, Monica Heintz explores these questions, drawing on case studies from Eastern Europe that encompass migration, religion, economic and social policies and paying particular attention to the way morality works in communities undergoing rapid social change. She uses these examples to reflect on the wider question of societal conflict and change, showing how they are driven by moral values. By highlighting the centrality of such values as engines for action and questioning the limits of universal moral values, she argues that anthropology has the capacity to shed light on the study of morality and moral values generally. The Anthropology of Morality: A Dynamic and Interactionist Approach will be of interest to students and researchers in anthropology, as well as those in politics and sociology with an interest in European politics."--Provided by publisher.